Pemberdayaan Ekonomi Masyarakat Melalui Pengembangan Pariwisata Dalam Perspektif Ekonomi Islam (Studi Di Pantai Biru Kersik Kecamatan Marang Kayu) - Desi Ratna Sari; N Norvadewi; Angrum Pratiwi (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
Efforts to empower the community's economy in the tourism sector have been regulated and contained in Law No. 10 of 2009. One of the areas that are currently empowering and developing tourism potential is Marang Kayu District, located in Kutai Kartanegara Regency, East Kalimantan Province. One of the attractions owned by Marang Kayu District is Blue Beach Kersik which is located in Kersik Village. The development of the potentials that exist on the beach has received attention from the government as seen from the selection of Kersik Village as one of the Tourism Villages in Kutai Kartanegara Regency, East Kalimantan. Community economic empowerment through tourism villages is expected to be able to contribute to the economy, either directly or indirectly to the local community and in improving social life. Judging from the purpose of this study, namely to find out the model of community economic empowerment through tourism development at Blue Beach Kersik and to determine community economic empowerment through tourism development at Blue beach Kersik in an Islamic economic perspective.This type of research is a field research and a descriptive qualitative approach. Sources of data in this study using primary data, in this study data collection techniques through observation, interviews with the informant Head of Kersik Village, Tourism Awareness Group which collected three people, and business owners who opened seven people. With data analysis techniques, namely data reduction, data presentation and conclusion drawing.Based on the results of this study, it shows that the model of community economic empowerment through the development of Blue Beach Kersik tourism is seen from the form of empowerment through micro, small and medium enterprises. empowerment strategy by developing a creative economy and the use of social media, community participants and the government. The economic independence of the community comes from the use of the beach in Kersik Village so that it has an impact on the community's economy. from the view of Islamic Economics that community economic empowerment through tourism development at Blue Beach Kersik has been carried out in a good way so as to provide benefits and welfare for people's lives.